PENDIDIKAN DAYAH MENJAWAB PROBLEMATIKA BANGSA: STUDI GAYA HIDUP SANTRI DAYAH BABUSSALAM - Teuku Zulkhairi (PIONIR: JURNAL PENDIDIKAN, 2021)
This article discusses the attitude of the santri in Dayah Babussalam Matangkuli, North Aceh. This attitude which is the result of the kitab kuning-based Islamic education process they received, both are lifestyle in the form of views and daily life routines that are lived. This model of the daily life of the students is the answer to the various problems that plague the Indonesian nation today. The writing of this article uses descriptive analysis method. The data collected is the result of observations, interviews and documentation which is then analyzed descriptively. The results showed that the santri in the pesantren have a number of lifestyles that can be ideal models for the life of the Indonesian nation. The attitude results from the educational process include simplicity, mutual help, ukhuwah Islamiyah, protected from the damage of illegal drugs and advances in information technology, mutual respect and so on. This santri lifestyle is expected to be an ideal model for the attitude of the younger generation of Indonesia.